Christian prisoners: fifth and sixth century inscriptions from Corinth - C. Breytenbach (Acta Theologica)
Among the inscriptions from Corinth (in publication), there are graffiti carved into the floor of a prison in Corinth. They shed interesting light on the hopes, beliefs and opinions of Christians from late antiquity. This study offers an overview of the insights to be gained from these graffiti. Now that IG IV² 3 Fasc. 3. Inscriptiones Corinthi, regionis Corinthiae is available, the evidence on Christian prisoners in the later Roman Empire will be easily accessible.2 The texts consist of graffiti on limestone floor tiles. They were found at the back of the “Boudroumi” arches.3 The vaults were shops north-west of the agora of ancient Corinth. Currently, these fragments of the limestone slabs that are still available are kept in the museum’s storerooms.